Unsuspected primary malignancy in the setting of elevated serum alpha-fetoprotein - Sarmast, Naveed (Proc (Bayl Univ Med Cent), 2019)
Hepatocellular carcinoma is the most common solid liver cancer and is screened for with serum alpha-fetoprotein (AFP) in patients with chronic hepatitis or cirrhosis. However, other tumors can produce AFP, and one of these is the “hepatoid” adenocarcinoma, arising in extrahepatic sites. We present a patient with chronic hepatitis C, multiple liver tumors, and a marked elevation in AFP who was mistakenly thought to have hepatocellular carcinoma, but primary hepatoid adenocarcinoma arising at the gastroesophageal junction was discovered at autopsy.